Mirror Electromyografic Activity in the Upper and Lower Extremity: A Comparison between Endurance Athletes and Non-Athletes - Maudrich, Tom; Kenville, Rouven; Lepsien, Jöran; Villringer, Arno; Ragert, Patrick; Steele, Christopher J. (Frontiers in Human Neuroscience, 2017)
During unimanual motor tasks, muscle activity may not be restricted to the contracting muscle, but rather occurs involuntarily in the contralateral resting limb, even in healthy individuals. This phenomenon has been referred to as mirror electromyographic activity (MEMG). To date, the physiological (non-pathological) form of MEMG has been observed predominately in upper extremities (UE), while remaining sparsely described in lower extremities (LE). Accordingly, evidence regarding the underlying mechanisms and modulation capability of MEMG, i.e. the extent of MEMG in dependency of exerted force during unilateral isometric contractions are insufficiently investigated in terms of LE. Furthermore, it still remains elusive if and how MEMG is affected by long-term exercise training. Here, we provide novel quantitative evidence for physiological MEMG in homologous muscles of LE (tibialis anterior (TA), rectus femoris (RF)) during submaximal unilateral dorsiflexion in healthy young adults. Furthermore, endurance athletes (EA, n=11) show a higher extent of MEMG in LE compared to non-athletes (NA, n=11) at high force demands (80%MVC). While the underlying neurophysiological mechanisms of MEMG still remain elusive, our study indicates, at least indirectly, that sport-related long-term training might affect the amount of MEMG during strong isometric contractions specifically in trained limbs. To support this assumption of exercise-induced limb-specific MEMG modulation, future studies including different sports disciplines with contrasting movement patterns and parameters should additionally be performed.